Identifikasi Penyebab Risiko dalam Analisa Mitigasi Risiko pada Rantai Pasok Obat-Obatan di Apotek XYZ dengan Menggunakan Metode House of Risk (HOR) - Fergisya, R. A. Luthfi Asia; Pulansari, Farida (Universitas Batanghari Jambi, 2025)
The supply chain in the pharmaceutical sector has an important role in ensuring the availability of drug supplies for pharmacies so that they can provide good care to patients. A smooth supply chain can increase the efficiency of a business's business processes, therefore it is necessary to carry out risk management to minimize the occurrence of risks that could hamper the smooth supply chain at Apotek K-24. The risk management method used is House of Risk (HOR). From House of Risk Stage 1, 18 risk events and 18 risk causes (risk agents) can be identified. Based on the analysis in House of Risk Phase 2, 12 risk mitigation strategies were obtained, including always updating news regarding diseases that are currently being experienced, always supervising the placement of medicines in warehouses, increasing supervision in pharmacies, increasing the amount of inventory from existing inventory, eliminating stock-related defects. medicines are in short supply, always supervise the placement of medicines on displays, carry out regular checks, make agreements with distributors regarding delivery times and limits on delivery delays, carry out planning by considering disease trends and sudden demand, improve communication with distributors, always monitor drug stock cards, carry out check again when receiving the goods.